2021
DOI: 10.1080/26395940.2021.1920468
|View full text |Cite
|
Sign up to set email alerts
|

A review of mercury pathological effects on organs specific of fishes

Abstract: Rapid development has been associated with mercury pollution in the aquatic environment, leading to mercury toxicity in fish and other aquatic organisms. Histopathological abnormalities such as hyperplasia, inflammation, and necrosis have been observed in various fish tissues as a result of mercury contamination based on organic mercury (methylmercury) and inorganic mercury (mercuric chloride) exposure via dietary or water exposure, respectively, with different duration doses of mercury. Knowing that tissue ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…For example, it was shown that only 4 days after the injection of 0.6 μg.g -1 of HgCl 2 , a concentration 88 ( A. saxatilis ) and 128 times ( A. bahianus ) lower than in the liver of Bouillante fishes, severe disorganisation and degradation were already observed in Gymnotus carapo liver tissues (Vergilio et al, 2012). More generally, seeing concentrations in livers, fishes of Bouillante probably also contains very high levels of Hg in their kidneys, gills and gut, which would occasion breathing problems, endocrine disruptions, starvation, acceleration of metabolism, and severe stress (Zulkipli et al, 2021). Moreover, our results reveal that sea urchins gonads contain abnormally high levels of mercury in Bouillante but a 20-30mn exposure to a 2.7-3.3 μg.L -1 of HgCl 2 has been shown to completely inhibit sperm fertilization capacities in another sea urchin species (Eissa, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was shown that only 4 days after the injection of 0.6 μg.g -1 of HgCl 2 , a concentration 88 ( A. saxatilis ) and 128 times ( A. bahianus ) lower than in the liver of Bouillante fishes, severe disorganisation and degradation were already observed in Gymnotus carapo liver tissues (Vergilio et al, 2012). More generally, seeing concentrations in livers, fishes of Bouillante probably also contains very high levels of Hg in their kidneys, gills and gut, which would occasion breathing problems, endocrine disruptions, starvation, acceleration of metabolism, and severe stress (Zulkipli et al, 2021). Moreover, our results reveal that sea urchins gonads contain abnormally high levels of mercury in Bouillante but a 20-30mn exposure to a 2.7-3.3 μg.L -1 of HgCl 2 has been shown to completely inhibit sperm fertilization capacities in another sea urchin species (Eissa, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Once accumulated, mercury may exert toxic effects on various biological pathways and alter immune responses, neuronal signalling, and osmoregulation, leading to organ failure (Yang et al,2020, Balali-Mood et al, 2021. In fish, mercury concentrates in organs such as the liver, muscle tissue, gills, kidney and brain through exposure to contaminated water or food (Morcillo et al, 2017, Zulkipli et al, 2021. Some fish populations thrive at sites with contaminant concentrations that elicit toxic responses in naive populations (Durrant et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Methylmercury (MeHg) is generated mostly in the anoxic benthos of aquatic ecosystems, and its lipophilicity allows it to accumulate and biomagnify rapidly through food webs and spread throughout the biosphere (Depew et al 2013;Lin et al 2021). The toxicological impacts of Hg to sh and aquatic life are systemic, causing damage to the gills, liver, intestines, reproductive organs, and brain (Zulkipli et al 2021). Of particular concern are the damaging impacts of MeHg on sh reproduction, speci cally the inhibition of gonadotropin-secreting cells, reduction in gonad size, reduced viability of gametes, and disruption to male and female reproductive function (Crump and Trudeau 2009).…”
Section: Introductionmentioning
confidence: 99%